Trends in the use of health services and their relationship with multimorbidity in Brazil, 1998–2013 - de Souza, Ana Sara Semeão (BMC Health Serv Res, 2020)
BACKGROUND: Chronic non-communicable diseases (NCDs) are the leading cause of multimorbidity. Access to effective and equitable health services that meet NCDs’ needs is still limited in many countries. This constitutes the main barrier to coping with NCDs, especially in minimising the suffering of those who are already sick. The present study aimed to identify the relationship between multimorbidity and the use of different health services in Brazil from 1998 to 2013. METHODS: This is a panel study using data from the health supplement of the National Household Sample Survey of 1998, 2003 and 2008 and data from the National Health Survey carried out in 2013. Three health service utilization outcomes were considered: 1. search for health services in the last 15 days (excluding dental services), 2. medical consultation in the previous 12 months and 3. hospitalisations over the last 12 months. Multimorbidity was assessed by counting the number of morbidities from a list of 10 morbidities. Poisson regression models stratified by sex were used to estimate the crude and adjusted prevalence ratios and their respective 95% confidence intervals for each outcome of health service use and multimorbidity, per year. RESULTS: There was an increase in the prevalence of demand for health services and medical consultations in the last 12 months between 1998 and 2013, regardless of the multimorbidity classification. The prevalence of hospitalisations has decreased over the study period and increased twofold in individuals with multimorbidity. Having multimorbidity increased the use of health services for the three outcomes under the study, being more expressive among men. CONCLUSIONS: This study found that individuals with multimorbidity have higher levels of use of health services. Better understand the multimorbidity epidemiology and the associated impacts on the use and costs of health services can increase the quality of care provided to these patients and reduce rising health care costs. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12913-020-05938-4.